2021
DOI: 10.1007/s12237-021-00985-4
|View full text |Cite
|
Sign up to set email alerts
|

The Overlooked Hybrid: Geographic Distribution and Niche Differentiation Between Spartina Cytotypes (Poaceae) in Wadden Sea Salt Marshes

Abstract: Whole genome duplications (WGDs) lead to polyploid specimens and are regarded as major drivers for speciation and diversification in plants. One prevalent problem when studying WGDs is that effects of polyploidization in ancient polyploids cannot be disentangled from the consequences of selective evolutionary forces. Cytotypic differences in distribution, phenotypic appearance and in response to surface elevation (determined by HOF-modeling) were identified in a relatively young taxa-group of a hexaploid F1-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 103 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…It has to be noted, that S. anglica is an invasive species in the European Wadden Sea (see for example Nehring and Hesse, 2008). Looking at the geographic distribution of Spartina cytotypes in the European Wadden Sea, the study by Granse et al (2022) showed, that along the western parts of the Wadden Sea, mainly the dodecaploid cytotype was present.…”
Section: Study Sitementioning
confidence: 99%
“…It has to be noted, that S. anglica is an invasive species in the European Wadden Sea (see for example Nehring and Hesse, 2008). Looking at the geographic distribution of Spartina cytotypes in the European Wadden Sea, the study by Granse et al (2022) showed, that along the western parts of the Wadden Sea, mainly the dodecaploid cytotype was present.…”
Section: Study Sitementioning
confidence: 99%